Relative leader-member exchange and employee voice: Mediating role of affective commitment and moderating role of Chinese traditionality. Issue 1 (1st April 2014) - Zhao, Hongdan
Abstract : Purpose: – This study aims to examine the effect of relative leader-member exchange (RLMX) on employee voice by developing a moderated mediation model. The model focuses on the mediating role of affective commitment underpinning the relationship between RLMX and employee voice, and the moderating role of Chinese traditionality in influencing the mediation. Design/methodology/approach: – We tested the model with data from 358 supervisor-subordinate dyads in a large Chinese company. Employees and their immediate supervisors provided data on separate questionnaires and on different occasions. And then, we used an identification number to match each employee questionnaire with the response of his/her immediate supervisor. Findings: – Results indicated that affective commitment fully mediated the positive relationship between RLMX and employee voice, even after controlling for personal leader-member exchange (LMX) quality. We also found that Chinese traditionality moderated the mediated relationship between RLMX and employee voice via affective commitment, such that the mediation was stronger for people lower, rather than higher, in Chinese traditionality. Research limitations/implications: – Testing the moderated mediation model helps to advance our theoretical understanding of the psychological mechanisms that underlie the effect of RLMX on employees' behaviour. Originality/value: – This empirical study provides preliminary evidence of the mediating role of affective commitment in the positive relationship between RLMX and employee voice. Our moderated mediation model also extends the existing finding by adding substantive moderators (Chinese traditionality) to explain how the effect of RLMX on employees' behaviours unfolds.